The Role of Occupational Emotional Labor Requirements on the Surface Acting–Job Satisfaction Relationship. (March 2016) - Bhave, Devasheesh P.; Glomb, Theresa M.
In this study we employ two distinct lenses of emotional labor—EL as occupational requirements and EL as intrapsychic processes of surface acting—and examine their relationship with job satisfaction. In a large, occupationally diverse sample, results indicate that occupational EL requirements are positively related to job satisfaction, whereas surface acting is negatively related to job satisfaction. Additionally, occupational EL requirements have a cross-level moderation effect on the relationship between surface acting and job satisfaction. Nonlinear effects are also observed for surface acting: the initial negative relationship of surface acting with job satisfaction is exacerbated at high levels of surface acting. Overall, this study enriches current research findings by incorporating the role of the occupational context, and provides insight into alternative evaluations of EL.